Multi-sender Broadcast Authentication in Wireless Sensor Networks - Ya Gao; Peng Zeng; Choo, Kim-Kwang Raymond (2014 Tenth International Conference on Computational Intelligence and Security, 2014)
Broadcast authentication, a fundamental feature in wireless sensor networks (WSNs), enables users to broadcast to multiple sensor nodes in an authenticated way. Symmetric-key-based μTESLA-like schemes are a popular solution due to their energy efficiency, but most schemes are not scalable (e.g. in terms of the number of senders). On the other hand, several schemes based on public key cryptography (PKC) are proposed to secure the multi-user broadcast in WSNs. However, the computation and communication overheads in the underlying PKC infrastructure restrict its implementation in resource-constrained WSNs. This paper presents an efficient scheme, which supports multi-sender broadcast authentication and allows dynamic addition of new senders. We delay disclosing the keys of the master key chain generated by the base station to authenticate the commitment of each sender's key chain. Considering that senders may be captured and compromised by adversaries in a hostile environment, our scheme also provides a mechanism to revoke the compromised senders' broadcast authentication capability.